Levels of α7 integrin and laminin-α2 are increased following prednisone treatment in the mdx mouse and GRMD dog models of Duchenne muscular dystrophy - Ryan D. Wuebbles; Apurva Sarathy; Joe N. Kornegay; Dean J. Burkin (The Company of Biologists, 2013)
SUMMARY Duchenne muscular dystrophy (DMD) is a fatal neuromuscular disease for which there is no cure and limited treatment options. Prednisone is currently the first line treatment option for DMD and studies have demonstrated that it improves muscle strength. Although prednisone has been used for the treatment of DMD for decades, the mechanism of action of this drug remains unclear. Recent studies have shown that the α7β1 integrin is a major modifier of disease progression in mouse models of DMD and is therefore a target for drug-based therapies. In this study we examined whether prednisone increased α7β1 integrin levels in mdx mouse and GRMD dog models and myogenic cells from humans with DMD. Our results show that prednisone promotes an increase in α7 integrin protein in cultured myogenic cells and in the muscle of mdx and GRMD animal models of DMD. The prednisone-mediated increase in α7 integrin was associated with increased laminin-α2 in prednisone-treated dystrophin-deficient muscle. Together, our results suggest that prednisone acts in part through increased merosin in the muscle basal lamina and through sarcolemmal stabilization of α7β1 integrin in dystrophin-deficient muscle. These results indicate that therapies that target an increase in muscle α7β1 integrin, its signaling pathways and/or laminin could be therapeutic in DMD.